Pengetahuan Tentang Gizi Terhadap Pertumbuhan Dan Perkembangan Gigi Tetap Pada Siswa/i Usia 9-12 Tahun Di SD GMIT Baumata Kecamatan Taebenu Kabupaten Kupang - Agusthinus Wali (CV. Ulil Albab Corp, 2022)
Nutritional knowledge includes knowledge about the selection and consumption of daily food properly, the selection and consumption of food ingredients affect a person's nutritional status. Nutritional status in general affects the growth and development of the body including the growth and development of teeth, poor nutritional status will have an impact on the growth and development of teeth and mouth such as the occurrence of dental malocclusion, the prevalence of caries. The method used in this research is descriptive, the research sample is all students aged 9-12 with a total of 44 people, the research instrument uses a questionnaire and an examination format. The results of this study showed that there was no relationship between knowledge about nutrition and nutritional status of permanent tooth eruption of subjects at SD GMIT Baumata and no relationship between nutritional status and eruption of permanent teeth of subjects at SD GMIT Baumata.